The Effect of Provision Decoged Leaves of Moringa, Red Ginger, Turmeric, Red Meniran, Cinnamon, and Sambiloto Towards Reduction of Blood Pressure in The Region Long Kali District, Paser Regency - Sekar Ningrum; Dewi Rahmawati; Fajar Prasetya (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Moringa leaves, red ginger, turmeric, red meniran, cinnamon, and sambiloto have compounds with antihypertensive activity. The study was to describe the characteristics and effect of decoction 6 plant compositions for reducing the systolic and diastolic blood pressure of respondents in Long Kali District. The method used is quasi-experimental for 7 days. The results show characteristics data respondents for hypertensive patients in Long Kali District occurred the highest in late adulthood (36-45 years) with a percentage of 65%, female sex with a percentage of 75%, family history (hypertension) with a percentage of 65%, other diseases (more than 1 disease) with a percentage of 30%, and BMI obesity I (23.0 – 29.9) 50%. Data on the effect of giving decoction 6 plant compositions had a significant effect for decreased systolic and diastolic blood pressure of pre-test and post-test which was able to reduce the average systolic blood pressure on the third day by 11.7 mmHg (p=0.000) and diastolic blood pressure of 7.2 mmHg (p=0.005) and on the seventh day was also able to reduce the average systolic blood pressure of 9.4 mmHg (p= 0.012) and diastolic blood pressure of 4.9 mmHg (p= 0.030).